Efficient preparation of graphene oxide-immobilized copper complex and its catalytic performance in the synthesis of imidazoles - Heidari, Shahram; Zarnegaryan, Ali; Dehbanipour, Zahra (Frontiers in Chemistry, 2023)
A highly efficient and recyclable catalyst, graphene oxide grafted phenylthiocarbamide Cu-complex (Cu-PTC@GO), has been synthesized. The prepared nanocatalyst has been identified by various analytical techniques such as TG, FT-IR, ICP-AES, BET, N2 adsorption-desorption SEM, EDX, and elemental mapping analysis. The; Cu-PTC@GO exhibits outstanding results in preparing various imidazoles with higher yields, reduced reaction time, ease of product separation, and a simple procedure. The catalyst demonstrated appreciable recyclability up to five successive runs, and there was no substantial loss in catalytic performance. The result shows that heterogeneous catalyst base GO performed high activity and excellent recyclability in synthesizing various imidazoles and their derivatives owing to the unique state of support of graphene oxide and the copper complex.